ARCHITECTURAL HERITAGE: RESTORATION THEORY, METHODS AND PROBLEMS OF RESTORATION AND PRESERVATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
In this article, the author examines the theoretical foundations, restoration methods, and practical examples. She explores the processes involved in the reconstruction and restoration of historic buildings, the challenges they face, and the importance of preserving these buildings for future generations.